2000
DOI: 10.2307/3871259
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Abscisic Acid Signaling by the Ethylene Response Pathway in Arabidopsis

Abstract: Although abscisic acid (ABA) is involved in a variety of plant growth and developmental processes, few genes that actually regulate the transduction of the ABA signal into a cellular response have been identified. In an attempt to determine negative regulators of ABA signaling, we identified mutants, designated enhanced response to ABA3 (era3), that increased the sensitivity of the seed to ABA. Biochemical and molecular analyses demonstrated that era3 mutants overaccumulate ABA, suggesting that era3 is a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
189
2
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(209 citation statements)
references
References 0 publications
13
189
2
5
Order By: Relevance
“…A plausible explanation for these ethylene effects and our ABA de®ciency data can be found in recent reports that ethylene appears to be a negative regulator of ABA action during germination (Beaudoin et al, 2000;Ghassemian et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…A plausible explanation for these ethylene effects and our ABA de®ciency data can be found in recent reports that ethylene appears to be a negative regulator of ABA action during germination (Beaudoin et al, 2000;Ghassemian et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Ethylene insensitive mutants such as etr and ein2 germinate less well or after a longer period of after-ripening than wild type (Bleecker et al, 1988;Beaudoin et al, 2000). The ein2 and etr mutants are hypersensitive to ABA (Beaudoin et al, 2000;Ghassemian et al, 2000), which agrees with the observation that ein2 mutants were isolated as abi1-1 suppressors. The ctr1 mutant, which is characterised by a constitutive ethylene response, appeared among mutants selected as enhancers of the ABA insensitive mutant abi1-1 and ctr1 monogenic mutants are also slightly ABA resistant (Beaudoin et al, 2000).…”
mentioning
confidence: 52%
“…These observations, in combination with the non-dormant phenotype of the ein2 abi3-4 double mutant indicated that ethylene negatively regulates seed dormancy by inhibiting ABA action (Beaudoin et al, 2000). However, Ghassemian et al, (2000) and Chiwocha et al (2005) showed that, in addition to signalling, the slightly more dormant ethylene insensitive mutants, such as ein2 and etr1-2 have higher ABA levels. The higher levels of germination promoting hormones indicate compensation effects.…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
“…Indeed, these mutants flowered earlier than their control counterparts. Ethylene is also known as a negative regulator of the ABA response during seed germination (Beaudoin et al, 2000;Ghassemian et al, 2000). In agreement with an antagonism between ethylene and oxylipins, lines overexpressing RD20 showed an increased responsiveness to ABA similar to ethylene-insensitive mutants.…”
Section: Rd20 Is Involved In Regulating Plant Developmentmentioning
confidence: 88%